2014
DOI: 10.1002/aqc.2480
|View full text |Cite
|
Sign up to set email alerts
|

Signal crayfish (Pacifastacus leniusculus) predation upon Atlantic salmon (Salmo salar) eggs

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…For instance, in Japan the invasive P. leniusculus is competitively superior to the native Cambaroides japonicus (De Haan, 1841), which may partially explain the displacement of this species (Nakata & Goshima, 2003;Usio, Konishi, & Nakano, 2001). Previous studies have shown that P. leniusculus and P. clarkii prey on various native species; for example, P. leniusculus can consume Atlantic salmon eggs under laboratory conditions and P. clarkii was found preying on Rhinella ornate, a frog species in Brazil (Banci, Viera, Marinho, Calixto, & Marques, 2013;Findlay, Riley, & Lucas, 2015;Loureiro et al, 2015;Rosewarne et al, 2016). In addition, burrowing behaviours of P. clarkii and P. leniusculus can lead to river bank erosion which increases the water turbidity (Correia & Ferreira, 1995;Faller et al, 2016;Holdich, James, Jackson, & Peay, 2014;Loureiro et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Japan the invasive P. leniusculus is competitively superior to the native Cambaroides japonicus (De Haan, 1841), which may partially explain the displacement of this species (Nakata & Goshima, 2003;Usio, Konishi, & Nakano, 2001). Previous studies have shown that P. leniusculus and P. clarkii prey on various native species; for example, P. leniusculus can consume Atlantic salmon eggs under laboratory conditions and P. clarkii was found preying on Rhinella ornate, a frog species in Brazil (Banci, Viera, Marinho, Calixto, & Marques, 2013;Findlay, Riley, & Lucas, 2015;Loureiro et al, 2015;Rosewarne et al, 2016). In addition, burrowing behaviours of P. clarkii and P. leniusculus can lead to river bank erosion which increases the water turbidity (Correia & Ferreira, 1995;Faller et al, 2016;Holdich, James, Jackson, & Peay, 2014;Loureiro et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To complicate this story, the diversity and abundance of predacious aquatic invasive species have increased globally, and each invasion has negative implications for fish eggs during incubation (Lederer et al, 2008;Morse, Baldridge, & Sargent, 2013). For example, Findlay, Riley, and Lucas (2015) reported that egg consumption by a single exotic crayfish species of Atlantic salmon (Salmo salar) eggs significantly increased mortality, especially when the predator population was composed of larger bodied individuals that could effectively excavate redds and extract eggs. Rusty crayfish Orconectes rusticus, native to the Ohio River basin (Momot, Gowing, & Jones, 1978), have now become a prolific invasive species in many tributaries and lakes across the Great Lakes basin (Olden, Mccarthy, Maxted, Fetzer, & Jake, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to roach (egg diameter = 1.0–1.6 mm; Pinder , ) and common bream (egg diameter = 2.0 mm; Pinder, ), barbel eggs and emerging larvae are much smaller (1.9 mm mean diameter and ≈12.5 mm total length (TL), respectively) than those of Atlantic salmon (5.5 mm mean diameter and ≈25 mm TL, respectively; Findlay, Riley, & Lucas, ). The depth of egg burial by barbel, which was replicated in this investigation, appears to be sufficient to prevent pre‐emergent predation by signal crayfish.…”
Section: Resultsmentioning
confidence: 99%
“…However, the removal of barriers to spawning migration can increase potential spawning area (Lucas & Baras, ). When used in conjunction with habitat improvements to increase egg/embryo burial depth and intra‐gravel survival, barrier removal could prove to be a more effective conservation measure than conventional invasive crayfish control/removal methods, which are often ineffective at reducing numbers (Findlay et al, ).…”
Section: Resultsmentioning
confidence: 99%